Analisis Kinerja Karyawan Pada Pengadilan Agama Jakarta Timur Menggunakan Metode Balanced Score Card (BSC) - Novita Putri Wattimena; Dedy Syahyuni; Lady Diana Warpindyastuti (Maeswara : Jurnal Riset Ilmu Manajemen dan Kewirausahaan, 2024)
This study aims to analyze performance in the East Jakarta Religious Court using this research method in the Balanced Score Card is a descriptive research that aims to clearly describe the analysis of employee performance through the analysis of growth and learning perspectives, customer perspective analysis, financial perspective analysis and internal business perspective analysis. The results of the research on the performance of employees of the East Jakarta Religious Court with the Balanced Score Card are quite good from the analysis of the internal business perspective of 9.09%, the analysis of the growth and development perspective of work discipline over the past 3 months by 20.5%, then in employees who are given training has increased over the past 3 years by 35.27% and employees who have left have decreased in the last 3 years by 10.82%, then the analysis of the financial perspective for the last 3 months by 0.804. In this study draws the conclusion that there is a significant influence between employee performance and the application of the Balanced Score Card. Because the East Jakarta Religious Court is still experiencing a decrease in outgoing employees because these 4 perspectives are considered not optimal